Caveolar Endocytosis Is Critical for BK Virus Infection of Human Renal Proximal Tubular Epithelial Cells - Moriyama, Takahito (American Society for Microbiology, 2007)
In recent years, BK virus (BKV) nephritis after renal transplantation has become a severe problem. The exact mechanisms of BKV cell entry and subsequent intracellular trafficking remain unknown. Since human renal proximal tubular epithelial cells (HRPTEC) represent a main natural target of BKV nephritis, analysis of BKV infection of HRPTEC is necessary to obtain additional insights into BKV biology and to develop novel strategies for the treatment of BKV nephritis. We coincubated HRPTEC with BKV and the cholesterol-depleting agents methyl beta cyclodextrin (MBCD) and nystatin (Nys), drugs inhibiting caveolar endocytosis. The percentage of infected cells (detected by immunofluorescence) and the cellular levels of BKV large T antigen expression (detected by Western blot analysis) were significantly decreased in both MBCD- and Nys-treated HPRTEC compared to the level in HRPTEC incubated with BKV alone. HRPTEC infection by BKV was also tested after small interfering RNA (siRNA)-dependent depletion of either the caveolar structural protein caveolin-1 (Cav-1) or clathrin, the major structural protein of clathrin-coated pits. BKV infection was inhibited in HRPTEC transfected with Cav-1 siRNA but not in HRPTEC transfected with clathrin siRNA. The colocalization of labeled BKV particles with either Cav-1 or clathrin was investigated by using fluorescent microscopy and image cross-correlation spectroscopy. The rate of colocalization of BKV with Cav-1 peaked at 4 h after incubation. Colocalization with clathrin was insignificant at all time points. These results suggest that BKV entered into HRPTEC via caveolae, not clathrin-coated pits, and that BKV is maximally associated with caveolae at 4 h after infection, prior to relocation to a different intracellular compartment.